Socio-cultural types of youth and leadership = Społeczno-kulturowe typy przywództwa wśród młodzieży - Abramowa, Maria A. (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In this article we analyze the ethno-cultural and gender specifics of leadership qualities formed among young people. In this study the author used such techniques as the analysis of value orientations by Shalom Schwartz and individual-typological characteristics research by Ludmiła N. Sobchik.
Keywords: przywództwo; lider; gender; kulturowe typy funkcjonowania; style współpracy; leadership; leader; cultural types of functioning; cooperation styles